Optimisation of the SHRIKHAND Incorporated with lemongrass (Cymbopogon Citratus) - Nelson, Angelika; Hossain, SK Aktar; Mor, Sonia; kumar, Deodeep (Indian Journal of Dairy Science, 2024)
Shrikhand is a fermented milk product prepared from Chakka, a finely ground sugar and flavouring ingredient. Fermentation is a process of adding value to raw materials by converting them with microorganisms and enzymes into a variety of products with different nutritional and sensory qualities. We are witnessing an upward trend in nutritional and therapeutic consciousness in the new millennium, which has raised consumer demand for fermented foods. The purpose of this study was to standardize the optimum level of lemongrass distillate in the manufacturing of Shrikhand, with the major goal of evaluating the product organoleptically, physico-chemically, and microbiologically. Shrikhand prepared with lemongrass distillate replacing sugar with jaggery powder (28%) used as a sweetener in Shrikhand. With a different ratio of lemongrass distillate @0.5%, 1% and 1.5%, and 28% jaggery powder is used as a sweetener. Shrikhand with 0.5% lemongrass distillate (T1) showed better sensory attributes as compared to others. The optimized product contains 38.24% carbohydrate, 8.34% protein, 11.90% fat, 0.99% ash, 59.37 % total solids, 40.63%moisture, 0.99%titratable acidity, 94.48% anti-oxidant activity, 0.04% crude fiber, 2.28mgVitamin C and 282.07 kcal Energy.Thus, product acceptability is judged by sensory evaluation, the best treatment can be rated as T2>T1>T0>T3.Keywords: Chakka, lemongrass distillate, Shrikhand, Antioxidant